A hybrid icebreaking resistance model to accommodate damage to the ice sheet - Bannish, David A. (Monterey, California: Naval Postgraduate School, 2013)
An analytical framework was constructed to interchange ice resistance components from existing ice resistance calculation methods. Within this framework, the Lindqvist analytical method bending ice resistance component was substituted with a value obtained from a finite element static model of the ice sheet. A parametric study of this substitution was performed with error correction to within 12% over the entire range of parameter variation. The finite element ice sheet model was then damaged; and then the average ice bending resistance was obtained, substituted into the Lindqvist analytical method, and quantified as a change in the total ice resistance. Therefore, a hybrid ice resistance model was developed that accounts for the effect of damage to the bending resistance component, and enables further study of unconventional icebreaking methods. Approved for public release; distribution is unlimited. Lieutenant Junior Grade, United States Coast Guard http://archive.org/details/ahybridicebreaki1094534623